The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1038/hr.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and safety of azilsartan with that of candesartan cilexetil in Japanese patients with grade I–II essential hypertension: a randomized, double-blind clinical study

Abstract: Azilsartan is a novel angiotensin receptor blocker being developed for hypertension treatment. This 16-week, multicenter, randomized, double-blind study compared the efficacy and safety of azilsartan (20–40 mg once daily by forced titration) and its ability to provide 24-h blood pressure (BP) control, with that of candesartan cilexetil (candesartan; 8–12 mg once daily by forced titration) in 622 Japanese patients with grade I–II essential hypertension. Efficacy was evaluated by clinic-measured sitting BP, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 20 publications
7
97
0
7
Order By: Relevance
“…Unlike candesartan which must be orally administered as a prodrug candesartan cilexetil to ensure adequate bioavailability, azilsartan has been shown to be effective in reducing BP when orally administered as either the ester prodrug, azilsartan medoxomil or as the primary compound. [29][30][31] During gastrointestinal absorption, azilsartan medoxidil is rapidly hydrolyzed to azilsartan, the bioactive molecule that selectively and competitively blocks angiotensin induced activation of AT1 receptor in an insurmountable fashion. 32,33 Azilsartan in clinically approved doses as azilsartan medoxomil has been shown to lower 24-hour BP in hypertensive patients significantly more than the maximum approved dose of olmesartan medoxomil, the later being considered by some to be one of the most potent ARBs for lowering BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike candesartan which must be orally administered as a prodrug candesartan cilexetil to ensure adequate bioavailability, azilsartan has been shown to be effective in reducing BP when orally administered as either the ester prodrug, azilsartan medoxomil or as the primary compound. [29][30][31] During gastrointestinal absorption, azilsartan medoxidil is rapidly hydrolyzed to azilsartan, the bioactive molecule that selectively and competitively blocks angiotensin induced activation of AT1 receptor in an insurmountable fashion. 32,33 Azilsartan in clinically approved doses as azilsartan medoxomil has been shown to lower 24-hour BP in hypertensive patients significantly more than the maximum approved dose of olmesartan medoxomil, the later being considered by some to be one of the most potent ARBs for lowering BP.…”
Section: Discussionmentioning
confidence: 99%
“…7 It has been reported that once-daily administration of azilsartan produced a more potent 24-h sustained antihypertensive effect than candesartan in Japanese patients with grade I-II essential hypertension, and it had an equivalent level of safety in a randomized, double-blind, comparative study. 8 It has also been reported that azilsartan provides greater BP reduction than candesartan over the entire 24-h monitoring period, as well as during the specific daytime, night-time, and early morning periods, by analysis of ambulatory blood pressure monitoring records. 9,10 Hence, this study was undertaken to evaluate whether the above-mentioned theoretical benefits actually translate into clinically observable benefits in patients of Grade I-II essential hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike candesartan which must be orally administered as a prodrug candesartan cilexetil to ensure adequate bioavailability, azilsartan has been shown to be effective in reducing BP when orally administered as either the ester prodrug, azilsartan medoxomil or as the primary compound. [23][24][25] During gastrointestinal absorption , azilsartan medoxidil is rapidly hydrolyzed to azilsartan, the bioactive molecule that selectively and competitively blocks angiotensin induced activation of AT1 receptor in an insurmountable fashion. 26,27 Azilsartan in clinically approved doses as azilsartan medoxomil has been shown to lower 24-hour BP in hypertensive patients significantly more than the maximum approved dose of olmesartan medoxomil, the later being considered by some to be one of the most potent ARBs for lowering BP.…”
Section: Discussionmentioning
confidence: 99%
“…сильнее снижает суточное систолическое артериальное давление (САД) и диа-столическое артериальное давление (ДАД), чем вал-сартан в максимальной дозе 320 мг. В работе Rakugi H, et al азилсартана медоксомил более эффективно снижал офисное и суточное АД, по сравнению с кан-десартаном [12], в исследовании Bönner G, et al [13] целевой уровень АД был достигнут у большего коли-чества пациентов, принимавших азилсартан, чем на фоне длительного приема рамиприла. В некото-рых доклинических исследованиях продемонстриро-ваны дополнительные свойства азилсартана [14].…”
Section: возможности комбинации азилсартана медоксомила и хлорталидонunclassified